Ephemeralization - Michael A. Fox (Oz, 2001)
Our capabilities of utilizing kinetics in architecture today can be extended far beyond what has previously been possible. This article looks at the potential of advanced kinetic architectural systems; what they are, what they can do for us, and how we can go about designing them.